Lithology of the Yastrebovsk deposits of the Lower Frasnian age and associated titanium placers of the Voronezh anteclise (Proceedings of Voronezh State University. Series: Geology, 2020)
Introduction: Deposits of the Yastrebovsk suite of the Lower Frasnian age contain volcanic-sedimentary titanium placers, unique in genesis and formed in the south east of the Voronezh anteclise (VA). A number of studies focus on the deposits, but the suite formed within the entire Paleozoic structure has not been thoroughly studied yet. The aim of this article is to fill this gap. Methodology: The deposits were studied using the lithological and facies analysis. The facie maps were based on the sections of several hundred wells. Results and discussion: The results of a detailed lithological characterization of the main types of Yastrebovsk deposits demonstrated that the formation of the studied sediments practically all over the studied territory occurred under coastal-marine and shallow-marine conditions with weak and medium activity of the hydrodynamic regime. In the south east of the Voronezh anteclise the formation occurred under lagoon and delta conditions. The article describes the characteristics of the titanium content of volcanic-sedimentary deposits in the south east of the studied area. Conclusions: Yastrebovsk deposits were formed under a warm moist climate with low-amplitude tectonic movements. The sea transgressed from the east, and ablation of terrigenous material occurred from the south and west. A characteristic feature of the studied deposits is an admixture of ilmenite-containing pyroclastic material from active volcanoes in the south east of the VA. Therefore, the volcanic-sedimentary rocks of the suite in this area are titanium-bearing. The thickness of the overburden is from 12–20 m to 181 m. The content of conditional ilmenite ranges from the a few kilograms to 389 kg/m 3. At the moment, industrial extraction of buried titanium placers is impractical due to the difficult mining conditions (high overburden capacity, water cut). However, they may well be extracted as an accompanying mineral during the integrated development of the existing copper-nickel deposits as well as during the development of open pits in order to obtain granite crushed stone.
Keywords: Yastrebovsk time; volcanic-sedimentary rocks; facies analysis; ilmenite; titanium placers